Pentingnya Budaya Etos Kerja dan Disiplin Kerja dalam Mendorong Kinerja SDM yang Unggul di Kantor Kecamatan Gunungguruh Sukabumi - Bonse Aris Mandala Putra Simangunsong; Maulita Lutfiani (CV. Lentera Literasi Indonesia, 2026)
The Importance of Work Discipline Culture in Encouraging Superior HR Performance. Work discipline culture in the work environment has a crucial role in influencing the performance of human resources (HR) in an organization. This article aims to identify the relationship between work discipline culture and superior HR performance. The research method used is a quantitative approach with a survey research design. The research population was all employees in medium-scale manufacturing companies in metropolitan cities. The research sample was taken using a purposive sampling technique, involving 100 respondents randomly selected from several key departments. The research instrument is a questionnaire that measures employee perceptions of work discipline culture and their performance. Data were analyzed using statistical regression techniques to determine the extent to which work discipline culture contributes to HR performance. The research results show that there is a significant positive relationship between work discipline culture and HR performance. These findings support the theory that the implementation of a strong work discipline culture can encourage better HR performance in the organization. The practical implication of this research is the importance of building and maintaining a positive work discipline culture as a strategy to improve HR performance and overall organizational productivity.